The Process of Schema Emergence: Assimilation, Deconstruction, Unitization and the Plurality of Analogies - Bingham, Christopher B.; Kahl, Steven J. (Academy of Management Journal, 2013)
Schemas are a central concept in strategy and organization theory. Yet, despite the importance of schemas, little is known about how they emerge. Our in-depth historical analysis of how groups in the life insurance industry developed their schema for the computer from 1945–1975 addresses this gap. We identify three key processes—assimilation, deconstruction, and unitization—that collectively explain and resolve an inherent tension related to schema emergence: how to make the unfamiliar familiar but conceptually distinct. We also find that each process relates to analogical transfer, but in a more pluralistic and dynamic way than the existing literature describes. Broadly, these findings have important implications for organizational change and managerial cognition.